2014
DOI: 10.2478/bvip-2014-0089
|View full text |Cite
|
Sign up to set email alerts
|

LC-MS/MS analysis of doxycycline residues in chicken tissues after oral administration

Abstract: For the purpose of quantitative determination of doxycycline (DC) residues in tissues, a sensitive liquid chromatographytandem mass spectrometry (LC-MS/MS) method was developed. The method was used to determine DC residues in chicken tissues (breast and thigh muscle, liver and kidney) after oral administration with drinking water to five-weak-old broiler chickens. The DC was administered for five consecutive days at a therapeutic dose of 10 mg/kg b.w. once a day. The tissues were collected after 6 h, 24 h, 7 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 18 publications
2
18
1
1
Order By: Relevance
“…The optimisations of instrumental parameters and sample preparation procedures were based on the available literature (8,10,14,15,29) and our experience with antibiotic residue analyses (4,16). The developed method provided quantitative doxycycline, enrofloxacin, and ciprofloxacin determination results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The optimisations of instrumental parameters and sample preparation procedures were based on the available literature (8,10,14,15,29) and our experience with antibiotic residue analyses (4,16). The developed method provided quantitative doxycycline, enrofloxacin, and ciprofloxacin determination results.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic exposure to traces of chemotherapeutics and antibiotics may interfere with the actions of other drugs that are intentionally administered for the treatment of animal infections. Although there have been studies of antibacterial compounds including doxycycline residue concentrations in different animal tissues (8,11,14,15,20,26,31,32,34), there is no information about the possible effects of constant exposure to trace amounts of previously used antibiotics on target antibiotics in chicken tissue. Therefore, this study elucidates the effects of constant trace amounts exposure on the residues of intentionally applied doxycycline in chicken breast, thigh, and liver.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier residue data on broilers with oral medication of 20 mg/kg body weight (BW) daily for 4-5 days indicated that the DC levels in muscle, liver and kidney on the 5th day after the final medication were all below their MRLs (Anadón et al, 1994;El-Gendi et al, 2010). Recently, one report of DC given at a lower dose (10 mg/kg) for 5 consecutive days indicated that the DC residue on the 7th day after drug withdrawal was also safe (Gajda et al, 2014). Nevertheless, tissue residue levels in possible extra-label use (double concentration) have not been investigated.…”
mentioning
confidence: 99%
“…Triethylamine is a very common additive used to block silanols groups in reversed-phase chromatography when separating basic analytes (21). Oxalic acid in a mobile phase shows a significant efficiency in softening the effect of residual silanols on the stationary phase and good TCs separation without tailing (6,16,24,30). However, it should be taken into account that mobile phases containing non-volatile compounds used in LC -MS or LC -MS/MS may cause clogging at the interface and a build-up of deposits in the ion source (26,27).…”
Section: Discussionmentioning
confidence: 99%